The effect of ball characteristics on head acceleration during purposeful heading in male and female youth football players - Peek, K.; McKay, M.; Fu, A.; Meyer, T.; Oxenham, V.; Esopenko, C.; Caccese, J.; Andersen, J. (Science and Medicine in Football, 2021)
Objective: The objective of this cross-sectional study was to explore the effects of different ball types and characteristics on head acceleration during purposeful heading in youth football players. Methods: Experienced male and female players (n = 61) aged between 12-17 years completed heading trials with 4 different balls (Ball 1 mass 192 grams (g), pressure 5.0 pounds per square inch (psi); Ball 2 432 g, 5.0 psi; Ball 3 255 g, 5.0 psi; Ball 4 430 g, 10.5 psi) whilst wearing a head-mounted accelerometer and gyroscope. Balls 1, 2 and 4 were size 5 balls; Ball 3 was a size 4 ball. Results: Multivariate analysis of variance and post-hoc univariate analyses revealed a statistically significant difference between ball type and head acceleration during heading for both linear acceleration (adjusted R2 = 0.68; F = 140.90; p = <0.001) and angular velocity (adjusted R2 = 0.28; F = 26.52; p = <0.001). Ball 1 (lightest size 5 ball) and Ball 3 (size 4 ball) demonstrated linear head accelerations up to 59% lower (p = <0.01) when compared with Ball 4 (size 5 regulated match ball). Discussion: Head acceleration during purposeful heading is influenced by changes to ball pressure, ball size and/or ball mass. Changing ball characteristics, particularly in youth football training when heading is being taught, should be an easy strategy to implement.